EXPERIMENTAL STUDY ON CUTTING ENERGY CONSUMPTION OF COAL MINING UNDER DIFFERENT WORKING CONDITIONS - HAO ZhiYong; ZHOU ZhengQi; ZHANG Pei; YANG QuanChun (Jixie qiangdu)
In order to study the cutting energy consumption characteristics of coal miner under complicated conditions, the MG500/1180-WD shearer was cut out under different working conditions by collecting the cutting energy consumption model of coal mining machine. Pin and idler axle load data, and finally through the different conditions of coal miners cutting energy consumption calculation, the following conclusions: to keep the other conditions remain unchanged, the linear cutting energy consumption with With the increase of the traction speed increase; the oblique cut cutting energy consumption value is far more than the straight cutting energy consumption value; shearer cutting energy consumption in addition to the speed of traction, cutting mode, but also by the impact of coal hardness, With the increase in the hardness of coal and cutting cutting energy consumption also increased. The results of this study provide the theoretical basis for the development and use of shearer, and provide the theoretical basis for the scientific and efficient production of coal mining industry.